Yetişkinlerde yılmazlığın yordanmasında pozitif şema ve koronavirüs kaygısının rolü - Özkök, Şerife (Hasan Kalyoncu Üniversitesi, 2021)
Yetişkinler hayatlarında birçok olumsuz yaşam olaylarına maruz kalmaktadır. Her yetişkin bu olaylar karşısında farklı düzeyde yılmazlık becerileri göstermektedir. Yılmazlık bireylerin geçmiş yaşantılarını içeren farklı değişkenlerden etkilenmektedir. Bu araştırmanın amacı ''Yetişkinlerde Yılmazlığın Yordanmasında Pozitif Şema ve Koronavirüs Kaygısının Rolü 'nün incelenmesidir. Araştırmaya toplam 237 kişi, 18 yaş üstü birey katılmıştır. Katılımcıların 154'ü kadın, 83'i erkektir. Veriler Yetişkin Yılmazlık Ölçeği, Pozitif Şema Ölçeği, Koronavirüs Kaygısı Ölçeği ve Kişisel Bilgi Formu aracılığıyla elde edilmiştir. Veri analizinde değişkenler arasındaki ilişkiyi belirlemek amacıyla Pearson Korelasyon Analizi ve bağımsız değişkenlerin bağımlı değişkeni sırasıyla ne ölçüde yordadığını belirlemek amacıyla hiyerarşik regresyon analizi kullanılmıştır. Araştırmada ilk olarak cinsiyetin yılmazlık ve pozitif şema alt boyutlarına göre fark-lılaşıp farklılaşmadığı incelenmiş, buna göre cinsiyetin yılmazlığın yalnızca iç kontrol odağı boyutunu açıklamada anlamlı bir fark oluşturduğu görülmüştür. Erkeklerin yılmazlık iç kontrol odağı boyutu kadınlara göre daha yüksek bulunmuştur. Araştırmanın asıl amacına yönelik yapılan hiyerarşik regresyon analizi bulgularına göre, ilk modelde kontrol edilen koronavirüs kaygısı yılmazlık aile ve sosyal ağlar boyutunu yordamada negatif yönde ve anlamlı katkı sağlamaktadır. İkinci modelde eklenen pozitif şema alt boyutları öz yetkinlik, başarı, güven, iyimserlik, değerlilik, yılmazlık öz yeterlik, iç kontrol odağı, aile ve sosyal ağlar, azim, başa çıkma uyum boyutlarını yordamada pozitif yönde ve anlamlı katkı sağladı-ğı görülmüştür. Koronavirüs kaygısı ve pozitif şema alt boyutları öz yetkinlik, başarı, güven, iyimserlik, değerlilik, yılmazlık öz yeterlik boyutunda toplam varyansın %53'ünü, iç kont-rol odağı boyutunda %24'ünü, aile ve sosyal ağlar boyutunda %18, azim boyutun-da %34'ünü, başa çıkma ve uyum boyutunda %16'sını açıklamaktadır. Sonuç olarak, koro-navirüs kaygısı ve pozitif şeman değişkenlerinin yılmazlığın anlamlı yordayıcısı olduğu belirlenmiştir.

Adults are exposed to many negative events during their life. Resilience is affected by different variables that including past experiences of individuals. The aim of this research is to review the "Role of Positive Schema and Coronavirus Anxiety in Predicting Resilience on Adults". 266 people that are over the age of 18 participated in the study. 178 of the participants were female and 88 of the participants were male. Datas were obtained according to Adult Resilience Scale, Positive Schema Scale, Coronavirus Anxiety Scale and Personal Informa-tion Form. Pearson Correlation Analysis was used to determine the relationship between the variables in the data analysis, and Hierarchical Regression Analysis was used to determine how the independent variables predicted the dependent variable, respectively. In the study, firstly, the effect of gender on resilience and positive schema sub-dimensions was examined, and it was seen that gender made a significant difference only for explaining ofthe internal locus of control dimension of resilience. In conclusion, the resi-lience internal locus of control dimension of men was found to be higher than that of wo-men. According to the hierarchical regression analysis results that made for main purpose of research, the coronavirus anxiety that controlled in the first model makes a negative and significant contribution to predicting of the resilience family and social networks dimen-sion. The positive schema sub-dimensions that added in the second model were made a posi-tive and significant contribution in predicting the dimensions of self-efficacy, success, con-fidence, optimism, worthwhileness, resilience self-efficacy, internal locus of control, family and social networks, perseverance, coping and adaptation. The positive schema sub-dimensions that added in the second model were made a positive and significant contribu-tion in predicting the dimensions of self-efficacy, success, confidence, optimism, worthwhi-leness, resilience self-efficacy, internal locus of control, family and social networks, perse-verance, coping and adaptation. Coronavirus anxiety and positive schema sub-dimensions explained for 53% of the total variance for dimensions of self-efficacy, success, confidence, optimism, worthiness, resilience, 24% of the total variance for dimensions of internal locus of control, 18% of the total variance for dimensions of family andsocial networks, and 34% of the total variance for dimensions of perseverance and lastly, 16% of the total variance for dimensions of coping and adaptation dimension. As a result, it was determined that corona-virus anxiety and positive schema variables were significant predictors of resilience.
Role of positive schema and coronavirus anxiety in predicting resilience on adults
Keywords: Psikoloji; Psychology